The Effect of Workload and Compensation on Employee Performance at PT. Toba Surimi Industries Medan - Vindica Leslie; Silvia Sofyan; Robin (Jurnal Mantik, 2022)
This study aims to determine the effect of workload and compensation on employee performance at PT. Toba Surimi Industries Medan. The population of this research is all employees who work at PT. Toba Surimi Industries Medan as many as 48 employees. Sampling using a saturated sample where the entire population will be used as a research sample. This type of research is descriptive quantitative and the nature of this reserch is explanatory research. In this study the questionnaire will be distributed as measured by a Likert scale. The data analysis model used is multiple linear regression and coefficient of determination as well as simultaneous and partial tests. The results showed that simultaneously the workload and compensation variables had an effect on the employee performance at PT. Toba Surimi Industries Medan. The results of the study partially the workload variable has no effect on the employee performance at PT. Toba Surimi Industries Medan. The results of the study partially the compensation variable has a positive and significant effect on the employee performance at PT. Toba Surimi Industries Medan. Based on this research, the implication for management is to further increase compensation and reduce workload.